Microstructural characterisation related to hot tearing of Al-Cu sand mould castings - M. Merlin (Fracture and Structural Integrity)
In this paper, the hot tearing behaviour in Al-(4.8?6)%Cu sand mould castings was preliminary investigated by means of microstructural examination and image analysis. A dog-bone pattern was employed for the realisation of the castings and three Al-Cu alloys with different Cu and Si contents were used. The effects of the alloy composition and of different pouring temperatures on the hot tearing behaviour of the castings were evaluated. The quantity of the eutectic phase available during solidification is considered a very important parameter for the crack healing phenomenon, in fact the eutectic liquid flows into the hot tear areas and covers parts of the cracks. The hot tear paths and surfaces were observed by means of optical and scanning electron microscopes, which showed that the fracture surfaces were dominated by bridged grain boundaries and the presence of a liquid film, in particular at higher copper concentrations. Several samples were also drawn from the zones characterised by the maximum cross-section variation and the micrographs from the optical microscope were statistically analysed by means of commercially available image analysis software. The quantitative microstructural parameters of percentage, mean area and distribution of the eutectic phase were evaluated and correlated to the capacity of the eutectic liquid to heal open fractures caused by hot tearing for the examined alloys.